2015
DOI: 10.5424/sjar/2015134-7622
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and nitrous oxide emissions from cattle-slurry and mineral fertiliser treated with nitrification inhibitor to an agricultural soil: A laboratory approach

Abstract: The application of organic and mineral fertilisers to soil can result in increased gaseous emissions to the atmosphere such as nitric oxide (NO) and nitrous oxide (N 2 O) gases. The aim of this study was to evaluate under laboratory conditions the effects on mineral N dynamics and NO and N 2 O emissions of application to soil of cattle slurry derived liquid fraction (LF) obtained by screw press and mineral fertiliser (MF), both treated with or without the nitrification inhibitor 3,4-dimethylpyrazole phosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Most studies investigating the use of NIs did not consider the mitigation effect on NO emissions, which can be significant after fertilization (Pereira et al, 2015). Several recent studies reported a wide range of NO mitigation effects ranging from 35 to 80% when the NI was applied with mineral fertilizer N or slurry (Akiyama et al, 2010;Pereira et al, 2015Pereira et al, , 2010.…”
Section: Effect Of Ni On N2o No and N2 Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies investigating the use of NIs did not consider the mitigation effect on NO emissions, which can be significant after fertilization (Pereira et al, 2015). Several recent studies reported a wide range of NO mitigation effects ranging from 35 to 80% when the NI was applied with mineral fertilizer N or slurry (Akiyama et al, 2010;Pereira et al, 2015Pereira et al, , 2010.…”
Section: Effect Of Ni On N2o No and N2 Emissionsmentioning
confidence: 99%
“…Most studies investigating the use of NIs did not consider the mitigation effect on NO emissions, which can be significant after fertilization (Pereira et al, 2015). Several recent studies reported a wide range of NO mitigation effects ranging from 35 to 80% when the NI was applied with mineral fertilizer N or slurry (Akiyama et al, 2010;Pereira et al, 2015Pereira et al, , 2010. In our study, application of the NI significantly reduced NO emissions at all three soil moisture conditions, which is likely due to the inhibition effect of NI on nitrification process, indicating that the overlooked mitigation effect of NI on NO emissions should be taken into account when evaluating NI's mitigation effect on GHG emissions.…”
Section: Effect Of Ni On N2o No and N2 Emissionsmentioning
confidence: 99%
“…After each incubation period, three soil cores were randomly removed from the incubator and were divided into two depths (0-75, 75-150 mm), to be immediately analyzed for mineral N. Ammonium and NO 3 − were extracted with 2 M KCl (1:5 w/v) and filtrate (Whatman 42) was analyzed for NH 4 + and NO 3 − concentrations by automated segmented flow s p e c t r o p h o t o m e t r y ( S a n P l u s , S k a l a r , B r e d a , The Netherlands). Net mineralizable-N was determined according to Carranca et al (2009) and Pereira et al (2015).…”
Section: Soil Mineral N Dynamicsmentioning
confidence: 99%